Quality Accreditation and Sustainable Development of Private Universities in Vietnam - Duong ThiAnh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article analyses the management policies of the Government and Ministry of Education and Training (MOET) on how quality accreditation has an impact on the sustainable development of private universities in Vietnam. A qualitative method approach was used in the research consisting of discourse analysis and interviews with five managers from the three targeted private universities. This study revealed that the majority of the university management board was to guide public universities as well as private ones to develop toward regional and international educational standards. It is also revealed from the study that private universities should pay more effort than public institutions in the same accreditation set of standards due to the disadvantages of human resource, the enrollment of students, research capacity and funding scheme.